The economics of open source software development - Bitzer, Jurgen, 1970-; Schroder, Philipp J. H. (Amsterdam ; Boston : Elsevier, 2006)
Open Source Software (OSS) development appears to present a stark contrast to traditional production and innovation methods and an unlikely contestant in the marketplace. Some of the most striking features are that OSS development is based on contributions of volunteer programmers, that these programmers only associated with each other through informal communities, that the resulting software products are made available for free, and that this unconventional development method is able to produce software of high complexity and extraordinary quality. Obviously, the emergence of software has fundamentally changed the software business. The simple facts that production is carried out by voluntary private programmers and that the marketable outcomes are supplied to consumers for free, have resulted in far-reaching effects on market structures, business models, and innovation processes in the software industry. While incumbents had to adapt their strategies to this newly emerging competition, OSS-based firms had to develop viable business models enabling them to generate profits. These fundamental changes in the software industry have subsequently attracted the interest of analysts, business people and research in economics and management science. *This book fills a substantial gap in this field *Serves as an invaluable reference for all those interested in OSS *The information is broad in scope.
The economics of open source software development : an introduction / Jurgen Bitzer and Philipp J.H. Schroder -- Decoding the free/open source software puzzle : a survey of theoretical and empirical contributions / Maria Alessandra Rossi -- Open source software : free provision of complex public goods / James Bessen -- Intrinsic motivations and profit-oriented firms in open source software : do firms practise what they preach? / Cristina Rossi and Andrea Bonaccorsi -- Business models and community relationships of open source software firms / Linus Dahlander and Mats G. Magnusson -- A statistical analysis of defects in Debian and strategies for improving quality in free software projects / Martin Michlmayr and Anthony Senyard -- Coworker governance in open-source projects / Christoph Lattemann and Stefan Stieglitz -- Bounty programs in free/libre/open source software / Sandeep Krishnamurthy and Arvind K. Tripathi -- An organizational perspective on free and open source software development / Sladjana Vujovic and John P. Ulhoi -- Linux vs. Windows : a comparison of application and platform innovation incentives for open source and proprietary software platforms / Nicholas Economides and Evangelos Katsamakas -- The impact of entry and competiton by open source software on innovation activity / Jurgen Bitzer and Philipp J.H. Schroder -- Application of social network analysis to the study of open source software / Jin Xu, Scott Christley, and Gregory Madey.
Includes bibliographical references and indexes.
Keywords: Computer software industry; Open source software -- Economic aspects; Computer software -- Development; Electronic books